Backcalculation of Finite-Element Modeling Based on Field Measurements Results of Excavation in Steel Sheet Pile Walls - Zoa Ambassa; Jean Chills Amba; Merlin Bodol Momha; Landry Djopkop Kouanang (Advances in Civil Engineering)
The study presents a development of a nonlinear finite element calculation technique for the prediction of the stability of the multistaged deep excavation in submerged multilayered soft soil retained by steel sheet pile walls structures performed from Cast3M FE code. Optimization numerical backcalculation results are given for the design and construction of retaining walls with adjustment parameters, horizontal displacements, and earth and hydraulic pressure measurements. The difficulties of modeling 2D sheet pile walls in 2D with irregular shapes were overcome by transforming the geometry and stiffness of these sheet steel sheet pile walls into retaining walls of equivalent bending stiffness on the one hand and regular geometric shapes on the other hand. The results of this approach are satisfactory in view of the horizontal displacement curves obtained on the steel sheet pile walls compared by the measures.